Metabolism of asparagine in the physiological state and cancer - Qiong Yuan; Liyang Yin; Jun He; Qiting Zeng; Yuxin Liang; Yingying Shen; Xuyu Zu (Cell Communication and Signaling, 2024)
Abstract Asparagine, an important amino acid in mammals, is produced in several organs and is widely used for the production of other nutrients such as glucose, proteins, lipids, and nucleotides. Asparagine has also been reported to play a vital role in the development of cancer cells. Although several types of cancer cells can synthesise asparagine alone, their synthesis levels are insufficient to meet their requirements. These cells must rely on the supply of exogenous asparagine, which is why asparagine is considered a semi-essential amino acid. Therefore, nutritional inhibition by targeting asparagine is often considered as an anti-cancer strategy and has shown success in the treatment of leukaemia. However, asparagine limitation alone does not achieve an ideal therapeutic effect because of stress responses that upregulate asparagine synthase (ASNS) to meet the requirements for asparagine in cancer cells. Various cancer cells initiate different reprogramming processes in response to the deficiency of asparagine. Therefore, it is necessary to comprehensively understand the asparagine metabolism in cancers. This review primarily discusses the physiological role of asparagine and the current progress in the field of cancer research.